The potential of obsidian "big data" - Mark Golitko (UISPP Journal)
Studies of obsidian provenance have been a core component of the archaeological sciences from the mid-1960s onward. With the growing application of portable X-ray Fluorescence Spectrometers (PXRF) in obsidian research, the number of such studies, and the amount of data generated per study, is rapidly increasing. Obsidian studies are on the verge of a “big data” revolution, and archaeologists should note the issues inherent to using such large datasets, including maintaining data quality and generating appropriate theoretical models. It is argued that network models and concepts represent one such framework in which the potential of larger obsidian datasets can be effectively harnessed by archaeologists and archaeological scientists.